Optimalisasi Aksi Bergizi: Meningkatkan Kesadaran Dan Status Gizi Remaja: Optimising the Nutrition Action Initiative: Enhancing Awareness and Nutritional Status among Adolescent Girls - Manaf, Abdul; Zamli, Zamli; Sainuddin, Sudirman (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
The problems of anaemia and malnutrition remain major challenges faced by adolescent girls in Indonesia, including in Kota Palopo. This community engagement programme aimed to improve awareness, knowledge, and nutritional status of adolescent girls through balanced nutrition education and the provision of Iron Supplement Tablets (TTD) at SMPN 10 Kota Palopo. The implementation methods included interactive counselling, group discussions, and supervised TTD consumption. The primary target was 50 adolescent girls, with the involvement of teachers, health professionals, and the Kota Palopo Health Office as partners. Evaluation was carried out through pre- and post-tests of knowledge as well as monitoring adherence to TTD consumption.  The results demonstrated a significant increase in students’ knowledge of balanced nutrition and anaemia, along with an improvement in adherence to TTD consumption from 80% to 95% after the programme. In addition, close collaboration was established between the school and the health office in promotive and preventive efforts for adolescent health. This programme strengthened cross-sectoral synergy, fostered a healthy living culture within the school environment, and served as a model intervention that could be replicated in other schools. Carefully planned educational interventions, involving various stakeholders and supported by continuous monitoring and evaluation, have proven effective in improving the health quality of adolescent girls. The main recommendation is the need for regular implementation of nutrition education and guidance in schools to ensure the sustainability of healthy behavioural changes among students.